Przestrzeń współczesnych bibliotek publicznych. Dworzec, palmiarnia, dom handlowy, pasaż miejski, kino...jako inspiracja = The Space of Contemporary Public Libraries. Train Station, Palm House, Department Store, City Passage, Cinema... As Inspiration - Buck, Andrzej (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
Contemporary libraries are most often organized as multimedia centers of knowledge, culture, and information. They are evolving, drawing inspiration from European, mostly Scandinavian, models. In addition to the traditional functions of libraries (information transfer, collection gathering, and preservation), they are beginning to implement a model of an open, hybrid li-brary focused on engaging with the community. The author discusses how these changes are taking place and whether the "identity of the public library" is being lost in the process, what the organizational culture of libraries looks like, and finally, whether these changes require a "new space" when the current one is suboptimal. He addresses questions such as: How to convince librarians to embrace change? How to engage the media in promoting new library services? What are the limits of the new offers? What should be done to ensure that the "third place" service does not overshadow what is most important in the library? The article discusses new spaces, functionalities, and services in libraries, using examples from Polish library practices. The author also explores issues related to the use of physical space (both urban and post-industrial) by contemporary libraries.
Keywords: biblioteka; modernizacja; zarządzanie; przestrzeń; oferta; technologia; architektura bibliotek; rola małych, średnich i dużych bibliotek publicznych; library; modernization; menagment; space; offers; technology; library architecture; role of small, medium and large public libraries